1997
DOI: 10.1212/wnl.48.2.394
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal change in basal ganglia volume in patients with Huntington's disease

Abstract: Cross-sectional MRI studies demonstrating an association between caudate atrophy and symptom severity and duration of symptoms in patients with Huntington's disease (HD) have been assumed to reflect longitudinal changes in basal ganglia, but such neuropathologic progression has never been directly demonstrated. Subjects in the current study were 23 HD patients at various stages of the disorder who had two MRI images at least 10 months apart (mean interimage interval = 20.8 months). We measured volumes of cauda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
136
2
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(154 citation statements)
references
References 12 publications
13
136
2
3
Order By: Relevance
“…Given the resilience of these findings, which have been demonstrated consistently across multiple studies in preHD,22, 23, 24, 25, 26, 27, 28, 29 we would suggest that analyses of subcortical volume becomes a minimum requirement for any future preclinical disease modifying trials in HD. Notably, structural volumetric analyses are likely to be more robust across scanners than resting‐state functional neuroimaging measures; therefore, they are also more likely to form a tractable basis for a standardized polymarker that can be used to integrate findings across studies and sites.…”
Section: Discussionmentioning
confidence: 73%
“…Given the resilience of these findings, which have been demonstrated consistently across multiple studies in preHD,22, 23, 24, 25, 26, 27, 28, 29 we would suggest that analyses of subcortical volume becomes a minimum requirement for any future preclinical disease modifying trials in HD. Notably, structural volumetric analyses are likely to be more robust across scanners than resting‐state functional neuroimaging measures; therefore, they are also more likely to form a tractable basis for a standardized polymarker that can be used to integrate findings across studies and sites.…”
Section: Discussionmentioning
confidence: 73%
“…Certainly the increased use of diagnostic imaging tools in the clinic indicates the growing value of anatomical visualization in clinical diagnostics. Already, characteristic neuroanatomical changes in several human diseases have been demonstrated (Aylward et al, 1997(Aylward et al, , 1998Gaser et al, 1999;Giedd et al, 1994;Hynd et al, 1991;Jack et al, 1997). However, it is important to note that the genetic homogeneity in studies of inbred mice presents a unique advantage that greatly improves the statistical power of mouse studies.…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale human studies of disease populations have revealed that imaging findings of this type are often characteristic of individual diseases or disease processes. Examples include schizophrenia [Gaser et al, 1999], Alzheimer disease [Jack et al, 1992[Jack et al, , 1997], Huntington's disease [Aylward et al, 1997[Aylward et al, , 1998Jernigan et al, 1991], and attention-defecit hyperactivity disorder [Giedd et al, 1994;Hynd et al, 1991]. Furthermore, symptoms detected by neuroimaging can frequently be correlated with behavioral manifestations of disease [Backman et al, 1997;Kwon et al, 2003;Hohol et al, 1997;Zivadinov et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…), was blinded to participant characteristics and completed all measurements for the study. Measurements were made by manually drawing boundaries of the caudate (head and body) and putamen, as previously described (Aylward et al, 1996;Aylward et al, 1997), and volumes were calculated based on the number of identified pixels. Caudate and putamen volumes were summed to obtain a measure of total striatal volume.…”
Section: Participant Characterizationmentioning
confidence: 99%